Structure and Process Modeling of Seemingly Unstructured Leisure-Travel Decisions and Behavior - Martin, Drew; Woodside, Arch (Emerald Group Publishing Limited, 2012)
Purpose – This paper aims to introduce a structuring and processing model (SPM) as a framework for tourism decision making research. Design/methodology/approach – The study employs McCracken's long interview to collect data in field settings. The study introduces advances in Mintzberg et al.'s approach to structuring seemingly unstructured decision making to explain travelers' decision-making processes. Findings – SPM enables mapping and comparing visitors' plans, motivations, choices, and consequences. The results demonstrate nuanced decision-behavior dynamics and complexities of visitors' travel-related unconscious/conscious thinking and behavior. Research limitations/implications – SPM does not attempt to generalize findings to large survey samples. Practical implications – Travel planning and execution dynamics dictate that a decision-making funnel metaphor in consumer research does not capture such trip complexity because additional decisions are made when the traveler arrives at the destination. Originality/value – SPM is dynamic and inclusive explaining simultaneous planning elements as well as considering sub-decisions occurring before and after different phases in the process. This model includes both conscious and unconscious internal retrievals as well as contextual influences relating to current planning affect the decision-making process.